The Influence of Digital Promotion and Lifestyle on Impulse Buying Behavior Among Millennial Users Of Tokopedia Paylater in Surabaya City - Deviana Nur Sholihah; Hesty Prima Rini (PT. Publikasiku Academic Solution, 2025)
This study aims to analyze the influence of digital promotion and lifestyle on impulse buying, as well as to test the role of financial literacy as a moderating variable in the millennial generation of Tokopedia PayLater users in Surabaya City. The research method uses a quantitative approach , with a problem-solving approach and data collection techniques using cluster techniques. Data analysis was carried out using SMARTPLS 4.0, due to the infinite population, so the researcher used the Lemeshow formula (1997) to determine a sample of 165 respondents with an infinite population of Tokopedia PayLater users. The results of the study indicate that digital promotion and lifestyle have a significant positive effect on impulse buying. Financial literacy is also proven to influence impulse buying and plays a moderating role in the relationship between digital promotion and lifestyle on impulse buying, although with varying moderating strengths. These findings indicate that financial literacy plays an important role in controlling impulsive buying behavior amidst the intense digital promotion and consumptive lifestyle of the millennial generation. This study is expected to be a reference for e-commerce platforms, policy makers, and users in improving wiser consumption behavior in the digital era.